Asymptomatic Carotid Surgery Trial-2 (ACST-2): Rationale for a randomised clinical trial comparing carotid endarterectomy with carotid artery stenting in patients with asymptomatic carotid artery stenosis. - Rudarakanchana, N; Dialynas, M; Halliday, A (Elsevier, 2009)
Objectives To compare carotid endarterectomy with carotid artery stenting in the prevention of stroke in patients with asymptomatic carotid stenosis. Design A large, simple, pragmatic international trial of at least 5000 patients with asymptomatic carotid stenosis in whom intervention is thought to be needed but where there is substantial uncertainty about the appropriate choice of treatment. The trial is designed to fit in easily with normal clinical practice. Materials and Methods A short (~2 min) telephone call is made to randomise patients to either carotid endarterectomy (CEA) or stenting (CAS). Follow-up by the collaborator will be at one month after the procedure (simple 1-page form) and by the ACST office for 5-years post-procedure. Data will be analysed on an intention-to-treat basis; main outcomes will be 30-day myocardial infarction, stroke and death, and 5-year stroke rates. In addition, appropriate subgroup analyses will be undertaken, and health economic evaluation will consider procedural and stroke-related healthcare costs and quality of life. Conclusion Collaborators who routinely undertake CEA and CAS are encouraged to participate in ACST-2. This trial, now funded and open for randomisation, will provide important evidence comparing the immediate and long-term safety and efficacy of carotid endarterectomy and stenting in patients with asymptomatic carotid stenosis.